DEIKSIS PADA NOVEL DALAM MIHRAB CINTA KARYA HABIBURAHMAN EL SHIRAZY - Unik Safitri; Sisilya Saman; Patriantoro Patriantoro (Universitas Tanjungpura, 2019)
AbstractThis research aimed to analysis more deeply in the form and meaning of deixsis person, place, and time of Dalam Mihrab Cinta novel by Habiburrehman El Shirazy. This was based on the problem in study: (1) how does the form of deiksis person, the place, and time, (2) how does the meaning of the deiksis person, place, and time, (3) how did the all three implementation plan of the deiksis in the learning Indonesia language. The research used descriptive method with the qualitative format. Data and source of data in this research was came from inter-character consists deixis person, place, and time dialogue in the novel Dalam Mihrab Cinta by Habiburrahman El Shirazy. Morever, this research used documentary tecniques in data collection. Based on the result of data analysis, it may be deduced that there was a deixsis person in the form of free morfem and tied morfem is proclitik and enklitik. There is a deixis place and time in the form of word and phrases. Then, the all format of the deiksis person, place, and time has the meaning of the lexicon and gramatical significance. Additionally, this study may also be used as material in Indonesia language learning curriculum 2013.Keywords: Deixis Person, Form, Meaning, Place, and Time.